Metode Maternal Reflektif Dalam Meningkatkan Kemampuan Interaksi Sosial Pada Anak - Dhina Widayati; Laviana Nita Ludyanti; Fifi Laylatul M (Prosiding SPIKesNas : Seminar Publikasi Ilmiah Kesehatan Nasional, 2022)
One of the problems that arise in deaf children is communication disorders that will affect the ability to social interaction so speech therapy needs to be given. The purpose of this research was to determine the effect of speech therapy on the ability to socially interact in deaf children. The design of this research used a pre-experiment with one group pre-post-test approach. The sample size was obtained through a purposive sampling technique using the Wilcoxon signed ranks test. The results obtained are P-value = 0.002 <a = 0.005, which means that there is an effect of giving speech therapy on the ability to social interaction in deaf children. This method consists of an approach from the heart to the heart, conversations reading audiovisual and transitional conversations making communication of deaf children easily which ultimately improves the process of social interaction. This therapy is expected to be used to improve social interaction in other children so that the development of children’s social personalities will be optimal.